Dampak Modernisasi terhadap Sistem Sosial Budaya Masyarakat Tani - Alfayubi Aria Buana; Muhammad Rizky Pratama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
Modernization has become a dominant force reshaping rural agrarian societies across the world, particularly traditional peasant communities. This article aims to analyze the impact of modernization on the socio-cultural systems of farming communities, focusing on changes in values, social relations, kinship structures, and cultural practices. The study employs a qualitative descriptive approach through a literature-based analysis of classical and contemporary scholarly works on agrarian transformation and peasant modernization. The findings reveal that modernization introduces significant transformations in production systems, social stratification, and cultural orientations of peasant societies. Traditional norms such as mutual cooperation, communal land management, and kinship-based social organization tend to weaken, while rational-economic behavior, individualism, and market-oriented values become more dominant. However, the study also finds that peasant communities demonstrate resilience by selectively adapting modern elements while preserving core cultural identities. This article concludes that modernization does not entirely eradicate peasant culture but rather reconstructs it through a complex process of negotiation between tradition and modernity. These findings contribute to sociological and agrarian studies by offering a comprehensive understanding of socio-cultural dynamics in modernizing rural societies.